Computer capacity utilisation - a multilevel perspective on decades of decline - Fevolden, Arne Martin (Technology analysis & strategic management, 2015)
This article uses a multilevel perspective to explain why there has been a dramatic decline in the utilisation of computer-processing power during the last two to three decades. It identifies that computers have been used in two different ways - either as single-user systems where each users received his or her own computer or as time-sharing systems where each computer was shared by several users. It finds that the time-sharing systems made considerably better use of the computers' resources than the single-user systems and that the utilisation of computer-processing power began to decline as single-user microcomputers began to replace time-shared minicomputers and mainframes. The article argues that this development contradicts much of the recent research on capacity utilisation, but argues that this contradiction can be explained by analysing this development as a transition process with multiple levels of interaction.